Adipokines and Osteoarthritis: Novel Molecules Involved in the Pathogenesis and Progression of Disease. (29th June 2011) - Conde, Javier; Scotece, Morena; Gómez, Rodolfo; Lopez, Veronica; Gómez-Reino, Juan Jesus; Gualillo, Oreste
Abstract : Obesity has been considered a risk factor for osteoarthritis and it is usually accepted that obesity contributes to the development and progression of osteoarthritis by increasing mechanical load of the joints. Nevertheless, recent advances in the physiology of white adipose tissue evidenced that fat cells produce a plethora of factors, called adipokines, which have a critical role in the development of ostearthritis, besides to mechanical effects. In this paper, we review the role of adipokines and highlight the cellular and molecular mechanisms at play in osteoarthritis elicited by adipokines. We also emphasize how defining the role of adipokines has broadned our understanding of the diversity of factors involved in the genesis and progression of osteoarthritis in the hope of modifying it to prevent and treat diseases.